Combining Mobile Technologies, Healthcare & Service Quality. A Bibliometric Analysis - Javed Ali; Ahmad Jusoh; Norhalimah Idris; Naveed Akhtar Qureshi; Saeed Abbas Shah; Alhamzah F. Abbas, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The purpose of the paper is to identify the links and connections among main themes of the search i.e., Mobile Technologies, Service Quality and Healthcare. It also aims at identifying the valuable contributions from authors, journals, countries, and institutions in the searched area. Data has been extracted from Scopus database and it covers the timeline from 2005 to 2021. The final documents (n=245) have been analysed through VOSviewer software and MS Excel. Results show that Guo, X., International Journal of Medical Informatics, Harbin Institute of Technology, China and United States are top performing author, journal, institution and countries respectively. According to the results for collaborations and associations, Bhuiya A., United States and Mobile Healthcare are the most prominent author, country and keyword with highest score of total link strength (TLS). Findings suggested important and valuable avenues for future research directions in terms of underperforming countries, under-utilized subject areas and under-explored themes (keywords). This study, to best of our knowledge, is the first of its kind in mapping the literature of combined themes (Mobile Technologies, Service Quality and Healthcare).